Determinants of service quality and its effect on customer satisfaction and loyalty: an empirical study of private banking sector - Islam, Rafikul; Ahmed, Selim; Rahman, Mahbubar; Al Asheq, Ahmed (Emerald Publishing House, 2021)
Purpose – The main purpose of this study is to investigate the impact of various service quality dimensions, namely reliability, responsiveness, visibility, employee commitment and access to service on customer satisfaction in the private banking sector of Bangladesh. The research also investigates the relationship between customer satisfaction and loyalty and effect of demographic variables on customer satisfaction. Design/methodology/approach – The researchers distributed 320 self-administered survey questionnaires among private banks’ customers in Bangladesh and obtained 200 useable responses with a 62.5% valid response rate. The research data were analysed using confirmatory factor analysis (CFA) and structural equation modelling (SEM) approaches. Analysis of variance and logistic regression have also been used to obtain the supplementary findings. Findings – The research findings indicate that visibility, responsiveness and employee commitment have positive and significant effect on customer satisfaction, whereas reliability and access to service are found to have insignificant influence on customer satisfaction of private banking services. The findings of this study also revealed that customer satisfaction has positive and significant relationship with customer loyalty. But except respondents’ occupation type, all other demographic variables have no statistically significant relation with customer satisfaction. Research limitations/implications – The research focused solely on the private banking sector of Bangladesh and thus the results may not be applicable to other service sectors. Originality/value – This study conducted on customers’ perception of private banking services based on extended service quality dimensions and its relationship with customer satisfaction towards loyalty. The present research findings are anticipated to offer the guidelines for improving the customer satisfaction and loyalty of private banking services in Bangladesh as well as other countries.